A bird survey in a transitional area between two major conservation hotspots in Southeastern Brazil - Sementili-Cardoso, Guilherme [UNESP] (2019)
Transitional areas may have higher species richness than those located within established environments, as these ecotones provide a variety of resources that facilitate the maintenance of specific fauna. However, they tend to be overlooked in wildlife surveys. In this context, the western region of the state of São Paulo in Brazil is important because it contains areas of ecological transition between 2 major conservation hotspots in Brazil: the Atlantic Forest and the Cerrado. We surveyed the avifauna in a transitional area between these domains, using qualitative and quantitative methods between December 2016 and February 2019. We documented 220 species, of which 7 are endemic to the Atlantic Forest and 4 are endemic to the Cerrado. In addition, we documented 9 species that are threatened at some level (regional, national, or global), demonstrating the high conservation value of this area for birds. Therefore, our results show the potential of transitional areas for maintaining regional biodiversity.